The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fpsyg.2018.00545
|View full text |Cite
|
Sign up to set email alerts
|

Weibo or WeChat? Assessing Preference for Social Networking Sites and Role of Personality Traits and Psychological Factors

Abstract: Research trying to understand individual difference in the use of different social networking sites (SNSs) is minimal. In the present study, we collected data from 714 college students in China (273 males) to assess how personality traits and psychological factors relate to excessive use of WeChat and Weibo. We found that excessive use of Weibo and WeChat correlated positively with neuroticism, loneliness, and external locus of control and negatively with agreeableness, social support, and social interaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 45 publications
(71 reference statements)
0
51
0
Order By: Relevance
“…Based on the above reported literature, we hypothesized that male gender would associate positively with actively posting (Hypothesis 1), whereas female gender would associate positively with viewing others' profiles (Hypothesis 2) (Haferkamp et al, 2012;Special & Li-Barber, 2012;Teppers et al, 2014;Wohn & Lee, 2013). Concerning personality traits, extraversion (Hypothesis 3), openness to experiences (Hypothesis 4), and neuroticism (Hypothesis 5) would associate positively with both actively posting and viewing others' profiles (Blackwell et al, 2017;Chen et al, 2016;Hou et al, 2018;Hughes et al, 2012;Liu & Campbell, 2017;Wee et al, 2017). Finally, since most literature on emotions seems to suggest a link between SNS usage and a lack of emotional abilities, we hypothesized that emotional intelligence would associate negatively with both actively posting and viewing others' profiles (Hypothesis 6; De Choudhury et al, 2013;Moreno et al, 2011;Oldmeadow et al, 2013;Schwartz et al, 2013).…”
Section: The Current Studymentioning
confidence: 94%
See 3 more Smart Citations
“…Based on the above reported literature, we hypothesized that male gender would associate positively with actively posting (Hypothesis 1), whereas female gender would associate positively with viewing others' profiles (Hypothesis 2) (Haferkamp et al, 2012;Special & Li-Barber, 2012;Teppers et al, 2014;Wohn & Lee, 2013). Concerning personality traits, extraversion (Hypothesis 3), openness to experiences (Hypothesis 4), and neuroticism (Hypothesis 5) would associate positively with both actively posting and viewing others' profiles (Blackwell et al, 2017;Chen et al, 2016;Hou et al, 2018;Hughes et al, 2012;Liu & Campbell, 2017;Wee et al, 2017). Finally, since most literature on emotions seems to suggest a link between SNS usage and a lack of emotional abilities, we hypothesized that emotional intelligence would associate negatively with both actively posting and viewing others' profiles (Hypothesis 6; De Choudhury et al, 2013;Moreno et al, 2011;Oldmeadow et al, 2013;Schwartz et al, 2013).…”
Section: The Current Studymentioning
confidence: 94%
“…The majority of research on the psychological correlates of SNS use and attitudes has focused on personality traits (Hou et al, 2018;Hughes, Rowe, Batey, & Lee, 2012;Liu & Campbell, 2017;Oldmeadow, Quinn, & Kowert, 2013;Pettijohn II, LaPiene, Pettijohn, & Horting, 2012;Pornsakulvanich, 2017;Ryan & Xenos, 2011). According to the widely-accepted Five Factor Model of personality (McCrae & Costa, 1999) individuals vary in terms of extraversion, neuroticism, openness to experiences, agreeableness, and conscientiousness.…”
Section: The Influence Of Personality On Sns Usagementioning
confidence: 99%
See 2 more Smart Citations
“…Montag et al (2015) reported correlations between SNUD and unspecified Internet-use disorder amongst Chinese and Taiwanese samples. Hou et al (2018) assessed how personality traits and psychological factors relate to excessive use of WeChat R and Weibo R . The results showed that addictive use of Weibo R and WeChat R correlated positively with neuroticism, loneliness, and external locus of control and negatively with agreeableness, social support, and social interaction.…”
Section: Social Network Use Disorder and Further Predisposing Variabmentioning
confidence: 99%